2021
DOI: 10.3390/jmse9010038
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Shore Profile Evolution after an Extreme Erosion Event—Palanga, Lithuania

Abstract: We report cross-shore profile evolution at Palanga, eastern Baltic Sea, where short period waves dominate. Cross-shore profile studies began directly after a significant coastal erosion event caused by storm “Anatol”, in December of 1999, and continued for a year. Further measurements were undertaken sixteen years later. Cross-shore profile changes were described, and cross-shore transport rates were calculated. A K-means clustering technique was applied to determine sections of the profile with the same devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(92 reference statements)
3
4
0
Order By: Relevance
“…A similar strong relationship (overall r = 0.66) was found between the storm surge height (H SL ) and the beach volume eroded (∆Q be ), but the correlation was stronger for the erosive that for the accumulative shore (r = 0.79 and r = 0.55, respectively). During the highest surges with H SL > 1.2 m AMSL, the average dune retreat was 3-8 m. The changes observed were very similar to those reported from other parts of the Baltic Sea coast (Basiński 1995, Suursaar et al 2003, Eberhards et al 2006, Tõnisson et al 2008, Koltsova, Belakova 2009, ryabchuk et al 2011, Kelpšaite-rimkiene et al 2021.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar strong relationship (overall r = 0.66) was found between the storm surge height (H SL ) and the beach volume eroded (∆Q be ), but the correlation was stronger for the erosive that for the accumulative shore (r = 0.79 and r = 0.55, respectively). During the highest surges with H SL > 1.2 m AMSL, the average dune retreat was 3-8 m. The changes observed were very similar to those reported from other parts of the Baltic Sea coast (Basiński 1995, Suursaar et al 2003, Eberhards et al 2006, Tõnisson et al 2008, Koltsova, Belakova 2009, ryabchuk et al 2011, Kelpšaite-rimkiene et al 2021.…”
Section: Discussionsupporting
confidence: 82%
“…The wind was also responsible for small accumulation on dunes during the surges observed. In periods between the highest surges, the beach and the foredune evolve and develop again in the accumulative shore sections (Jarmalavicius et al 2016, Castelle et al 2017, Kelpšaite-rimkiene et al 2021, as was observed during the 21 years of observations on the Świna Gate Sandbar shore.…”
Section: Discussionsupporting
confidence: 53%
“…The K-means algorithm is a simple and popular clustering approach used in various applications [39]. It is a point-based clustering approach that starts with cluster centers located initially in arbitrary locations and goes through each stage of the cluster center to reduce the cluster error [39][40][41]…”
Section: Clusterizationmentioning
confidence: 99%
“…Nuyts et al [4] clarified the trends of topographical changes in the Rossbeigh coastal barrier in Dingle Bay, Ireland, using detailed analyses of 19-year data from the global navigation satellite system, bathymetry surveying, and an external force observation system. Moreover, Kelpšaitė-Rimkienė et al [5] revealed the characteristics of the cross-shore profile change in the Palanga coast of the East Baltic Sea through the skillful analysis of topographic survey data and wind data using K-means Clustering Technique, and calculation of the cross-shore sediment transport rate.…”
Section: Coastal Beach Change By Large Wavesmentioning
confidence: 99%